Blindness and Poverty - M. Saleh Memon, Zahid Hussain Awan, P.S. Mahar (Pakistan Journal of Ophthalmology, 2011)
Visual impairment or loss of vision is considered to be the most feared disability. This stems from the fact that since ancient times, the sense of sight is thought to be the most important sense. In addition to being a serious public health concern, it also has a great impact on the social and economic wellbeing of an individual. Blindness as a condition has fascinated man throughout history and continues to do so. In some cultures the blind is thought to be blessed with divine and psychic powers while in others blindness is considered a form of punishment for improper moral or social conduct.